2016
DOI: 10.1021/jacs.6b02575
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Images of Antimicrobial Peptides Provide Reflections on Their Functions and Amyloidogenic Properties

Abstract: Enantiomeric forms of BTD-2, PG-1, and PM-1 were synthesized to delineate the structure and function of these β-sheet antimicrobial peptides. Activity and lipid-binding assays confirm that these peptides act via a receptor-independent mechanism involving membrane interaction. The racemic crystal structure of BTD-2 solved at 1.45 Å revealed a novel oligomeric form of β-sheet antimicrobial peptides within the unit cell: an antiparallel trimer, which we suggest might be related to its membrane-active form. The BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 66 publications
6
54
1
Order By: Relevance
“…AMPs have been a prominent candidate for the development of new peptide‐based antimicrobials due to their various positive attributes . Reports on the self‐assembly properties of AMPs and antimicrobial activity of some amyloid structures provide a hint about the relationship between these two classes of peptides . It has been reported that diphenylalanine self‐assemblies have antibacterial activity and selective toxicity towards bacterial cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs have been a prominent candidate for the development of new peptide‐based antimicrobials due to their various positive attributes . Reports on the self‐assembly properties of AMPs and antimicrobial activity of some amyloid structures provide a hint about the relationship between these two classes of peptides . It has been reported that diphenylalanine self‐assemblies have antibacterial activity and selective toxicity towards bacterial cells .…”
Section: Discussionmentioning
confidence: 99%
“…3 Reports on the self-assembly properties of AMPs and antimicrobial activity of some amyloid structures provide a hint about the relationship between these two classes of peptides. 30,62 It has been reported that diphenylalanine self-assemblies have antibacterial activity and selective toxicity towards bacterial cells. 63 Therefore, in this study, Conventionally, amyloids have always been associated with disease conditions and toxic potentials.…”
Section: Discussionmentioning
confidence: 99%
“…The mixed topology was inspired by a recent crystallization study of a θ-defensin AMP, which found a mixed-topology trimer wherein one dimer had NCNC parallel topology and the other NCCN antiparallel topology (Fig. 1) 50 .…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that homochirality is required to create biopolymers with af unction. [9,10] Peptide molecules that can mimic large proteins are biologically active building blocks for the production of self-assembled nanostructures. [8] This suggests that homochirality plays ac ritical role for the structure and function of such systems,i ncluding sustaining self-replications cycles,however, chirality guided interactions between peptide molecules in the context of functionality are rarely explored.…”
Section: Determiningtheenigmaoftheoriginoflifeiscontroversialmentioning
confidence: 99%